2021
DOI: 10.1002/smll.202102975
|View full text |Cite
|
Sign up to set email alerts
|

Protein Nanopore Membranes Prepared by a Simple Langmuir–Schaefer Approach

Abstract: Filtration through membranes with nanopores is typically associated with high transmembrane pressures and high energy consumption. This problem can be addressed by reducing the respective membrane thickness. Here, a simple procedure is described to prepare ultrathin membranes based on protein nanopores, which exhibit excellent water permeance, two orders of magnitude superior to comparable, industrially applied membranes. Furthermore, incorporation of either closed or open protein nanopores allows tailoring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Such assemblies at the oil–water interface using transmembrane proteins are of interest to generating protocells because the channel of FhuA might act as a gateway in and out of the protocell, thereby mimicking real living cells. Moreover, we demonstrated that polymeric protein membranes can be formed by directly cross-linking FhuA with glutaraldehyde …”
Section: Fhua In Nanobiotechnology and Materials Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Such assemblies at the oil–water interface using transmembrane proteins are of interest to generating protocells because the channel of FhuA might act as a gateway in and out of the protocell, thereby mimicking real living cells. Moreover, we demonstrated that polymeric protein membranes can be formed by directly cross-linking FhuA with glutaraldehyde …”
Section: Fhua In Nanobiotechnology and Materials Designmentioning
confidence: 99%
“…Another exciting application of FhuA is the possibility of incorporating FhuA into polymers, ,,,, as already discussed above. A catalytically active membrane can be constructed by incorporating a FhuA-based artificial metalloenzyme into a polymer matrix .…”
Section: Fhua As a Protein Scaffold For Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation